Decision making, interest intermediation, and value: In government, public, and private agencies corporatism for work promotion - Esien Eddy Bruno (DANUBE: Law, Economics and Social Issues Review, 2020)
This paper analysis decision making, interest intermediation, and value in the realm of government, public and private cooperation under corporatism to enable young third-country immigrants' transition to work in Austria, Finland and the Czech Republic. Based on document analysis, this paper concludes a centralized delegation of authority, interest intermediations, and public values administrative devices in corporatism governance with democratic deficit that steer young third-country immigrants transition to work. However, the Czech Republic is dissimilar to Austria and Finland with the focus on relationship and partnership cooperation pattern to build contacts, where as Finland and Austria prefer cooperation in the form of coordinating varying employment objectives. The outcome points to deliberate democracy in neoliberal market-oriented setting. This is relevance to bureaucratic accountability and performance monitoring, but imperative to operational risk that may not only impair vulnerable people's belongings, but jeopardize public value accountability, sustainable finance and democratic values.
Keywords: 330; Corporatism; Third-Country Nationals; Employment System; Interest Intermediation; Institutions; Decision Making